Kesejahteraan Psikologis Pada Pengendara Ojek Online Di Kota Surakarta - Adelina Murti Syafiina; Andressia Yeiza Putri; Desy Rosiana; Emalia Yunika; Monika Ayu Pramesti; Riska Nabillaahadyah; Yuliana Setyaningrum (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2024)
Transportation is a crucial element in people's daily lives. The use of public transportation, particularly online motorcycle taxis, has become a significant alternative in fulfilling mobility needs. The rapid development of the online transportation industry demands further understanding of its impact on the psychological well-being of drivers. Online motorcycle taxi drivers face the risks of traffic accidents and emotional pressure during their duties. The psychological well-being of drivers has significant implications for their productivity and daily lives. This research aims to comprehend the psychological well-being of online motorcycle taxi drivers, with a focus on aspects such as self-acceptance, social relationships, autonomy, self-control, life goals, and personal growth. The study utilizes a descriptive qualitative approach and was conducted in the city of Surakarta. The results indicate that positive aspects like self-acceptance, positive relationships, autonomy, environmental mastery, clear life goals, and personal growth contribute to the psychological well-being of online motorcycle taxi drivers. Social support also plays a crucial role in enhancing their psychological well-being. Further research should involve other variables related to psychological well-being and expand the study to various online motorcycle taxi companies for a more holistic understanding.